Freezing Test for Evaluating Relative Frost Susceptibility of Various Soils. - Kaplar,Chester W. (1974)
The report presents a description of the equipment and procedures used in the laboratory test of the relative frost susceptibility of different soils on Corps of Engineers construction projects and includes typical results of freezing tests of natural soils. The test uses a slow unidirectional freezing of a 6-in. high, remolded or undisturbed soil specimen with water available at the base (open system). The heaving rate measured during the test is used as the basis for classification of the frost susceptibility potential of the soil. This type of test, which measures heaving rate, is considered most versatile and adaptable for evaluating the effects of numerous soil parameters on frost heave. (Author)